Characteristics of the Main Indicators of Peripheral Blood in Adolescents in the Tomsk Region - Ivan A. Deev; Ivan L. Kolomeets; Elena M. Kamaltynowa; Evgenii S. Kulikov; Alena N. Levko; Kristina V. Kulikova; Viktoriya I. Jurkova (Педиатрическая фармакология)
Background. The adolescent period is characterized by the features of growth and development of the organism when the risk of a number of diseases increases under the conditions of hormonal adjustment and under the influence of environmental factors. Objective. Our aim was to determine the reference values of the main values of peripheral blood and the prevalence of anemia in adolescents residing in the territory of the Tomsk region. Methods. We studied the results of medical examination of children aged from 13 to 16 years. To determine the main values of the general blood test (erythrocytes, hemoglobin, leukocytes, erythrocyte sedimentation rate), an automatic hematological analyzer was used. Evaluation of physical development was carried out by standard methods. The analysis of the results was carried out considering the sex, living conditions, weight, height, and body mass index. Results. We analyzed the values of peripheral blood of 7,120 adolescents. Rated values corresponded to the conventional age norms. The hemoglobin level and the number of erythrocytes are associated with the body weight, height, and body mass index of the respondents. Anemia of varying severity was recorded in 618/7,120 (8.7%) adolescents. More often anemia was verified in rural areas (OR 1.52; CI 95% 1.28–1.80) as well as in females (OR 2.62; CI 95% 2.18–3.15). Conclusion. Regional features of peripheral blood values and the prevalence of anemia in adolescents of the Tomsk region have been determined.